Combination of Direct Oval Window Vibroplasty With Customized Partial Ossicular Replacement Prosthesis (PORP): A Novel Reconstruction Technique to Rehabilitate Mixed Hearing Loss. Issue 10 (9th December 2021) - Grueninger, Ivo; Canis, Martin; Spiegel, Jennifer L.; Müller, Joachim
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Hearing rehabilitation with an active middle ear implant (AMEI) in patients with mixed hearing loss (MHL) after multiple ear surgeries is surgically challenging and requires individual solutions in some cases. Our objective was to introduce a feasible novel technique for direct oval window vibroplasty (OW vibroplasty) using a partial ossicular replacement prosthesis (PORP) to ensure stability and enable active and passive sound transmission. Design: Four patients with MHL following multiple middle ear surgeries and indication for an AMEI received direct OW vibroplasty in combination with a customized PORP between the enwrapped actuator and reconstructed tympanic membrane (TM). Results: Postoperative bone conduction was stable in all patients. All patients benefitted from the AMEI in combination with PORP with a mean functional gain of 31.5 ± 17.0 dB. Mean aided postoperative pure tone average was 27.3 ± 2.6 dB. Speech discrimination in quiet at 65 dB with the German Language Freiburg Monosyllabic Test improved for all patients to 68.8 ± 6.3% and in noise with the German Language Oldenburger Sentence Test to –10.4 ± 3.3 dB SNR. No complications were observed. Conclusions: This novel technique of direct OW vibroplasty extends the portfolio of reconstructive middle ear procedures by combining an intraoperatively customized "off-the-shelf" PORP as a coupler between floating mass transducer (FMT) and a cartilage TM. We found satisfying functional hearing results. Benefits of the reported technique comprise 1) stabilization and optimized coupling of the reconstruction, 2) possibility of passive sound transmission, 3) general feasibility due to great availability of a regular PORP, and 4) flexibility in bridging of large gaps between TM and actuator.